Results of a randomized controlled pilot trial of intravascular renal denervation for management of treatment-resistant hypertension. (2nd November 2017) - Jacobs, Lotte; Persu, Alexandre; Huang, Qi-Fang; Lengelé, Jean-Philippe; Thijs, Lutgarde; Hammer, Frank; Yang, Wen-Yi; Zhang, Zhen-Yu; Renkin, Jean; Sinnaeve, Peter; Wei, Fang-Fei; Pasquet, Agnès; et al.
Abstract: Objective: Previous trials of catheter-based renal-artery denervation (RDN) as treatment modality in resistant hypertension (rHT) generated unconvincing results. In the Investigator-Steered Project on Intravascular Denervation for Management of Treatment-Resistant Hypertension (INSPiRED; NCT01505010), we optimized selection and management of rHT patients. Methods: With ethical clearance to randomize 18 patients, three Belgian hypertension centers screened 29 rHT patients on treatment with ≥3 drugs, of whom 17 after optimization of treatment (age <70 years; systolic/diastolic office blood pressure (BP) ≥ 140/90 mm Hg; 24-h BP ≥130/80 mm Hg; glomerular filtration rate [eGFR] ≥ 45 mL/min/1.73 m 2 ; body mass index <40kg/m 2 ) were randomized and 15 were analyzed 6 months later, while medical treatment was continued ( n  = 9) or combined with RDN by the EnligHTN™ multi-electrode system ( n  = 6). Results: The baseline-adjusted between-group differences amounted to 19.5/10.4 mm Hg (change in control vs. intervention group,  +7.6/+2.2 vs. −11.9/−8.2 mm Hg; P  = .088) for office BP, 22.4/13.1 mm Hg (+0.7/+0.3 vs. −21.7/−12.8; mm Hg; P  ≤ .049) for 24-h BP, the primary efficacy endpoint, and 2.5 mL/min/1.73 m 2 (+1.5 vs. −1.1 mL/min/1.73 m 2 ; P  = .86) for eGFR, the primary safety endpoint. At 6 month, ECG voltages and the number of prescribed drugs ( P  ≤ .036) were lower in RDN patients, but quality of life and adherence, captured by questionnaire and urine analysis were similar in both groups. Changes in BP and adherence were unrelated. No major complications occurred. Conclusions: The INSPiRED pilot suggests that RDN with the EnligHTN ™ system is effective and safe and generated insights useful for the design of future RDN trials.